A relação entre workaholism e conflito trabalho-família mediadas pela carreira caleidoscópica - Moreira, Martiele Gonçalves (2024)
The current work context, characterized by connectivity, flexibility, and instability, has significantly increased the challenge of balancing professional and family demands and managing one's career. Considering this situation, the thesis is put forth that career decisions can be supported by different parameters (Kaleidoscopic Career) to address the individual and family needs of a worker, with different career choices potentially resulting in distinct consequences both professionally (Workaholism) and within the family (Work-Family Conflict). This thesis aimed to investigate the influence of career decisions, following the parameters of the Kaleidoscopic Career, on the relationships between Workaholism and Work-Family Conflict (WFC), from the perspective of Brazilian workers. To this end, three sequential and interdependent studies were conducted. The first study aimed to identify research gaps through a Systematic Literature Review, revealing the need for the application of new measures for Workaholism that were quantitatively reliable, and also outlining a list of study suggestions divided among individual, organizational, and methodological areas. Subsequently, the second study identified the development of a recent scale on Workaholism that addressed various weaknesses of existing ones. Accordingly, this scale was translated and adapted for the Brazilian context. As a result, an adapted scale for measuring Workaholism in the Brazilian context was obtained, which could be used across various professional fields. The third study utilized this already validated and adapted instrument and, through survey research, aimed to identify the mediation of the Kaleidoscopic Career in the relationship between Workaholism and Work-Family Conflict. It was possible to identify important results for deepening the theoretical debate on individuals' management regarding life spheres and possible consequences at the personal, relational, and organizational levels. As general findings, it was possible to verify that two out of the three parameters of the Kaleidoscopic Career influence the perception of Workaholism and Work-Family Conflict. These findings are novel and warrant further investigation to corroborate or refute them. However, based on the results of this thesis, it can be inferred that the life stages defined here by the parameters of the Kaleidoscopic Career influence the presence and development of workaholic behaviors and how Work-Family Conflict is perceived.